2016
DOI: 10.1039/c6cc06889h
|View full text |Cite
|
Sign up to set email alerts
|

DNA nanotechnology for nucleic acid analysis: multifunctional molecular DNA machine for RNA detection

Abstract: The Nobel prize in chemistry in 2016 was awarded for 'the design and synthesis of molecular machines'. Here we designed and assembled a molecular machine for the detection of specific RNA molecules. An association of several DNA strands, named multifunctional DNA machine for RNA analysis (MDMR1), was designed to (i) unwind RNA with the help of RNA-binding arms, (ii) selectively recognize a targeted RNA fragment, (iii) attract a signal-producing substrate and (iv) amplify the fluorescent signal by catalysis. MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 75 publications
1
41
0
Order By: Relevance
“…In recent studies, we have demonstrated innovative approaches to further improve the sensitivity of BiDz assays via multicomponent nucleic acid assemblies that “trap” substrate molecules near sites of BiDz assembly and unwind RNA analytes (Cox et al 2016a; Cox et al 2016b). We have also recently reported a proof-of-principle study for an alternative visual, colorimetric readout which would be ideal for point-of-care implementation (Gerasimova et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, we have demonstrated innovative approaches to further improve the sensitivity of BiDz assays via multicomponent nucleic acid assemblies that “trap” substrate molecules near sites of BiDz assembly and unwind RNA analytes (Cox et al 2016a; Cox et al 2016b). We have also recently reported a proof-of-principle study for an alternative visual, colorimetric readout which would be ideal for point-of-care implementation (Gerasimova et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…(A) Binary DZ (BiDZ) sensor for fluorescence detection of specific DNA or RNA analytes. 7 DNA strands DZa and DZb hybridize to a targeted analyte and form a DZ catalytic core, which cleaves a fluorophore (F) and a quencher (Q) labelled F-sub followed by separation of F from Q associated with an increased fluorescence. (B) Three EV71-specific fragments (targets I, II and III) were chosen to be targeted by the DZ OR gate, which consisted of 3 series of BiDZ sensors: DZ-I, DZ-II and DZ-III.…”
Section: Figmentioning
confidence: 99%
“…1A). 7 BiDZ consists of two DNA strands DZa and DZb, which hybridize to a targeted analyte and form a catalytic core of RNA-cleaving DZ. The DZ cleaves a fluorophore and a quencher labelled fluorogenic substrate (F-sub, Table S3, ESI † ), followed by an increase in fluorescence.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Each MHP component serves a specific function, thus enabling simultaneous improvement of multiple key characteristics. My presentation will cover the design of a probe that can differentiate single nucleotide substitutions in DNA in the entire temperature interval of 5-40 °C [1]; molecular machine that tightly binds the RNA analyte while remaining highly selective [2]; a strategy for the recognition of highly variable viral genomes with high selectivity [3].…”
mentioning
confidence: 99%